Party Formation and Coalitional Bargaining in a Model of Proportional Representation - Siddhartha Bandyopadhyay; Mandar Oak (Fondazione Eni Enrico Mattei (FEEM), 2004)
We study a game theoretic model of a parliamentary democracy under proportional representation where `citizen candidates' form parties, voting occurs and governments are formed. We study the coalition governments that emerge as functions of the parties' seat shares, the size of the rents from holding office and their ideologies. We show that governments may be minimal winning, minority or surplus. Moreover, coalitions may be `disconnected'. We then look at how the coalition formation game affects the incentives for party formation. Our model explains the diverse electoral outcomes seen under proportional representation and integrates models of political entry with models of coalitional bargaining.
Keywords: C72; D72; H19; 330; Proportional representation; Party formation; Coalitions; Ökonomische Theorie der Demokratie; Spieltheorie; Koalition; Regierungskoalition; Theorie